A Qualitative Exploration Of Perceptions Among Patients And Health Care Professionals Towards Smoking Cessation Treatment Failure And Process And Economic Outcome Assessment Of Pharmacist Managed Quit Smoking Clinic In The State Of Malacca, Malaysia - Lee, Mei Lin (2012)
Treatment default among smokers hinders the effectiveness of cessation service delivery. While most studies predicted the defaulters’ characteristics, the reasons these smokers dropped out and remain smoking are seldom explored. Thus, this qualitative component of this study aimed to explore these reasons by examining the barriers encountered by such smokers and their respective healthcare providers (HCPs). Social Cognitive Theory was used as the conceptual framework for the phenomenological qualitative study. From May 2010 to March 2011, 15 current adult smokers and nine HCPs from two Quit Smoking Clinics (QSCs) in Melaka Tengah District, Malacca were interviewed.